TRIPUSAT PENDIDIKAN SEBAGAI BASIS SOSIALISASIDAN PEMBENTUKAN KARAKTER SISWA - Nugroho, Puspo (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
The changes of globalization characterized by the industrial age or millennial-era influence and impact on bergesernya and the socialization processes in various areas. The shift from how to interact, communicate and socialize very pronounced so it's not uncommon to go beyond the limits of values and social order. These changes provide the impact of poitif but also the negative impact. Tripusat basic education becomes primary for strengthened back role and functions so that the goals of the national education system could be realized. This study more study library with scientific measures put forward in answering each question. From this study obtained how is the role of tripusat education kaitanya in the process of socialization as a means of forming the character of students. Keywords: Tri Pusat Education, Socialization, The Formation Of Base Characters